1957
DOI: 10.1136/oem.14.4.266
|View full text |Cite
|
Sign up to set email alerts
|

Absence and the Physical Conditions of Work

Abstract: The early studies of the Health of Munition Workers Committee and of the Industrial Fatigue Research Board clearly demonstrated the effects of conditions of work on lost time. Loveday (1917) showed that when hours of work were long absence increased and that this was particularly marked on heavy work. Vernon (1920) Walker, 1956). However, the relative importance of these factors can only be assessed after the effects of the physical conditions on absence have been determined. It therefore seemed desirable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1958
1958
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Also common, however, are nonsignificant relationships (Baumgartel & Sobol, 1959;Cooper & Payne, 1965 [2 samples]; Nicholson et al, 1977 [8 samples]). Other relationships that have occurred include Ushaped (Hedges, 1977;Kossoris, 1948;Nicholson et al, 1977;Shepherd & Walker, 1957), negative (Blumberg, 1980;Kossoris, 1948;Taylor, 1967a;Weaver, 1970), and inverted-U (Collins, 1962). Testing for other than linear relationships is important in view of the Nicholson et al study in which nonsignificant correlations were reported for four samples of continuous process workers, yet a Neuman-Keuls test revealed a curvilinear relationship.…”
Section: Absenteeismmentioning
confidence: 99%
See 1 more Smart Citation
“…Also common, however, are nonsignificant relationships (Baumgartel & Sobol, 1959;Cooper & Payne, 1965 [2 samples]; Nicholson et al, 1977 [8 samples]). Other relationships that have occurred include Ushaped (Hedges, 1977;Kossoris, 1948;Nicholson et al, 1977;Shepherd & Walker, 1957), negative (Blumberg, 1980;Kossoris, 1948;Taylor, 1967a;Weaver, 1970), and inverted-U (Collins, 1962). Testing for other than linear relationships is important in view of the Nicholson et al study in which nonsignificant correlations were reported for four samples of continuous process workers, yet a Neuman-Keuls test revealed a curvilinear relationship.…”
Section: Absenteeismmentioning
confidence: 99%
“…Avoidable absence has generally been found to be inversely related to age in male samples (Bernardin, 1977 [2 samples]; Hill, 1967;Nicholson et al, 1977 [9 samples]; Taylor, 1967aTaylor, , 1967bTucker & Lotz, 1957;Walker & de la Mare, 1971 [3 samples]). However, positive (Baumgartel & Sobol, 1959;Buzzard &Shaw, 1952;Cooper & Payne, 1965 [2 samples]), U-shaped (de la Mare & Sergean, 1961;Hedges, 1977;Shepherd & Walker, 1957), inverted-U-shaped (Collins, 1962;Isambert-Jamati, 1962), and nonsignificant relationships (Baumgartel & Sobol, 1959;Cooper & Payne, 1965 [2 samples]; de la Mare & Sergean, 1961;Gordon, Emerson, & Pugh, 1959;Ivancevich & McMahon, 1977;Metzner & Mann, 1953;Nicholson et al,.1977 [3 samples]; Taylor, 1967a) have also been reported for male avoidable absence. The Nicholson et al (1977) study included two measures of avoidable absence for 12 samples.…”
Section: Absenteeismmentioning
confidence: 99%
“…Two often-neglected (e.g., Steers & Rhodes, 1978) groups of variables connected to the physical well-being of the employee are relevant for an absence model. The first is related to the job situation and comprises the variables shift work (Nicholson, Jackson, & Howes, 1978;Philipsen, 1969) and working conditions (Gadourek, 1965;Liddell, 1954;Philipsen, 1969;Shepherd & Walker, 1957). The second group of variables is connected with the length of absence spells.…”
Section: Attendance or Absence Model?mentioning
confidence: 99%
“…Heaviness was rated from 1 for very heavy work to 7 for very light work, and temperature of the work situation as 1, 2, and 3 for hot conditions, some heat, and normal respectively. For further discussion of the procedure see Shepherd and Walker (1957). Ratings on most jobs were made by more than one person and the agreement between judges was found to be high.…”
Section: Sources Of Data and Sampling Methodsmentioning
confidence: 99%